Gut-Lung Microbiota in Chronic Pulmonary Diseases: Evolution, Pathogenesis, and Therapeutics - Chang Yi Shi; Chen Huan Yu; Wen Ying Yu; Hua Zhong Ying (Canadian Journal of Infectious Diseases and Medical Microbiology)
The microbiota colonized in the human body has a symbiotic relationship with human body and forms a different microecosystem, which affects human immunity, metabolism, endocrine, and other physiological processes. The imbalance of microbiota is usually linked to the aberrant immune responses and inflammation, which eventually promotes the occurrence and development of respiratory diseases. Patients with chronic respiratory diseases, including asthma, COPD, bronchiectasis, and idiopathic pulmonary fibrosis, often have alteration of the composition and function of intestinal and lung microbiota. Gut microbiota affects respiratory immunity and barrier function through the lung-gut microbiota, resulting in altered prognosis of chronic respiratory diseases. In turn, lung dysbiosis promotes aggravation of lung diseases and causes intestinal dysfunction through persistent activation of lymphoid cells in the body. Recent advances in next-generation sequencing technology have disclosed the pivotal roles of lung-gut microbiota in the pathogenesis of chronic respiratory diseases. This review focuses on the association between the gut-lung dysbiosis and respiratory diseases pathogenesis. In addition, potential therapeutic modalities, such as probiotics and fecal microbiota transplantation, are also evaluated for the prevention of chronic respiratory diseases.